A finite element analysis of load distribution during donning and orthostatic posture in the ITOP hybrid subischial socket. Issue 2 (25th April 2023) - Frigo, Carlo A.; Bellomo, Silvia; Bigatti, Matteo; Pellegrini, Roberto; Denza, Gabriele; Di Stanislao, Eugenio
Abstract : Introduction: Pressure and shear stresses applied to the stump of a transfemoral amputee wearing a newly designed prosthetic socket have been analyzed by a finite element modeling approach. Methods: The new socket was developed by the Istituto Tecnico Ortopedico Preneste, and it was named the "hybrid subischial socket." This work aimed at understanding the loads' distribution on the stump surface in 2 operative conditions: at the end of the wearing phase and during the orthostatic posture. The model of the stump was composed of 4 different materials: the femoral bone, the muscle tissue, the fat, and the skin layers. Except for the bone (rigid), the biological tissues were modeled as Neo-Hookean, and their mechanical properties were taken from the literature. The socket was composed of a containment frame, made of carbon fiber composite material, a shell made of flexible silicone, and a liner made of hyperelastic silicone. Results: The results of our simulation show that the main support areas are located in a proper position, in agreement with the ideal principles of this prosthetic design, and the maximum pressures are well below the pain threshold reported in the literature for the same contact areas. Conclusions: We can conclude that although the upper rim of the socket is well below the ischiatic area, the new socket design allows for a safe and comfortable support of the body weight. This is in agreement with the evidence of a good functionality and acceptance of this prosthetics gathered in the many real applications.